Analisis Kesenjangan Keterampilan Lulusan S1 dengan Kebutuhan Industri 4.0 dan 5.0 di Indonesia - Febriyani Kistianingrum; Izzaty Khoirunnisa; Soviya Fitriyani; Sri Mulyeni (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
This study aims to investigate the skill gaps experienced by bachelor’s degree graduates in Indonesia when facing the dual demands of Industry 4.0 and Society 5.0. The method applied in this research is a systematic literature review, synthesizing findings from 21 scientific articles focusing on the dynamics of skill gaps and the effectiveness of higher education interventions in Indonesia. The study findings reveal two main categories of competency gaps. In the context of Industry 4.0, the most significant deficiencies are observed in specific hard skills, particularly data literacy, artificial intelligence proficiency, and automation across various sectors. Meanwhile, within the Society 5.0 dimension, deeper gaps emerge in soft skills and human-centered competencies, including complex problem-solving, emotional intelligence, creativity, and environmentally sustainable skills. These human-centered skill gaps play a critical role in enhancing graduate value as AI technologies increasingly replace routine tasks. Although the Merdeka Belajar Kampus Merdeka program shows positive outcomes in improving sustainability skills and digital certification, it has not fully succeeded in driving fundamental transformation of higher education learning outcomes, limiting alignment with sustainability principles and the Society 5.0 approach. It can be concluded that Indonesian higher education faces the challenge of undertaking fundamental curriculum reform to integrate human-centered competencies as a foundation for preparing future human resources.